Skin manifestations in patients with covid-19: A literature review - Gunawan, Danny; Stella, Maureen Miracle; Sidharta, Veronika Maria (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2022)
Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. In December 2019, cases of pneumonia with unknown cause were first reported in Wuhan, Hubei Province, China. Confirmed cases and death rates due to COVID-19 in the world are still increasing. One part of the body that is affected and causes clinical symptoms in COVID-19 is the skin. This review aims to describe and analyze cutaneous manifestation in COVID-19. This study method is a review of the literature sourced from Google Scholar and PubMed. The literature was selected using English language criteria, using the clinical study method in the form of case reports. Meanwhile, literature review, systematic literature, and meta-analysis were excluded. Journal searches were carried out using the keywords